High cohesive toughness two-component epoxy interface adhesive for ultra-high performance concrete and preparation method thereof

CN122941337APending Publication Date: 2026-10-20CHONGQING JIANZHU COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611289218.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但是,现有普通环氧界面胶普遍存在三大缺陷:一是对UHPC致密低孔隙的表面浸润性差,难以渗透进入UHPC表层微结构形成机械咬合力;二是胶层与UHPC的模量匹配性差,在荷载作用下界面易出现应力集中导致脱粘;三是潮湿低温施工环境下粘结强度衰减严重,难以满足户外工地的复杂工况需求

Benefits of technology

[0015]本发明的有益效果: 本发明的用于超高性能混凝土的高粘结韧性双组分环氧界面胶及其制备方法,从浸润、化学键合、应力缓释三个方面强化UHPC界面粘接性能,该双组份环氧界面胶可在0℃低温和潮湿UHPC界面正常固化,实现0~35℃宽温度范围固化,胶液可充分浸润UHPC致密微孔界面,胶层韧性高、模量与UHPC基体匹配,与UHPC的高模量特性形成良好匹配,荷载作用下可有效分散界面应力,避免胶层脆性开裂,固化收缩低,冻融老化后粘接性能保留率高,经过50次冻融循环后粘结强度保留率仍高于90%。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a high-adhesion-toughness two-component epoxy interface adhesive for ultra-high performance concrete, comprising component A and component B. Component A, by weight, comprises the following components: 80-120 parts bisphenol A type epoxy resin E-51, 10-20 parts reactive diluent, 5-15 parts telechelic reactive liquid rubber, 18-28 parts fumed silica, 0.5-3 parts wetting and dispersing agent, and 0.5-3 parts coupling agent. Component B, by weight, comprises the following components: 20-40 parts modified phenolic amine, 5-15 parts polyamide, and 0.5-3 parts accelerator. [The text abruptly ends here, likely due to an incomplete sentence or missing information.] This two-component epoxy interface adhesive enhances the interfacial bonding performance of UHPC through three aspects: chemical bonding, stress relief, and chemical bonding. It can cure normally at the UHPC interface in low temperature and humidity at 0℃, achieving a wide temperature range of 0~35℃. The adhesive can fully wet the dense microporous interface of UHPC, and the adhesive layer has high toughness and modulus that matches the UHPC matrix, forming a good match with the high modulus characteristics of UHPC. Under load, it can effectively disperse interfacial stress, avoid brittle cracking of the adhesive layer, and has low curing shrinkage. It also has a high retention rate of bonding performance after freeze-thaw aging, with a bond strength retention rate of over 90% after 50 freeze-thaw cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of interface bonding materials for ultra-high performance concrete (UHPC), specifically to a two-component epoxy interface adhesive with high bonding toughness for ultra-high performance concrete and its preparation method. Background Technology

[0002] Ultra-high performance concrete (UHPC) is characterized by ultra-high strength, high density, and low porosity, and is widely used in bridges, prefabricated buildings, and special structures. The interface between new and old UHPC, the splicing of precast UHPC components, and the interface between UHPC and ordinary concrete are typical weak points in reinforcement, repair, and prefabricated engineering. The hardened UHPC matrix is ​​dense and low-porosity, and there is no secondary hydration bonding between new and old UHPC. Furthermore, the elastic modulus of UHPC and ordinary concrete differs significantly, leading to inconsistent deformation under alternating loads and temperatures, and stress concentration easily occurs at the interface. Physical treatments such as roughening and sandblasting of the substrate surface alone are insufficient to achieve a long-term reliable interface bond; microcracks easily develop at the interface, leading to delamination and hollowing defects. Therefore, a specialized epoxy interface adhesive is needed as a transitional bonding layer. Through multiple functions such as microporous wetting and anchoring, chemical bonding, and stress buffering toughening, it eliminates interfacial weaknesses and achieves high-performance, high-durability integrated bonding between UHPC-UHPC and UHPC-ordinary concrete. However, existing ordinary epoxy interface adhesives generally have three major defects: First, they have poor surface wettability to the dense, low-porosity UHPC, making it difficult to penetrate into the microstructure of the UHPC surface to form mechanical interlocking force; second, the modulus matching between the adhesive layer and UHPC is poor, and stress concentration at the interface under load can easily lead to debonding; third, the bond strength decays severely in humid and low-temperature construction environments, making it difficult to meet the complex working conditions of outdoor construction sites. Moreover, most of the publicly available epoxy interface adhesive formulations are not customized for the special interfacial characteristics of UHPC. Ordinary toughening systems tend to sacrifice the heat resistance of the adhesive layer, and conventional coupling agents are difficult to simultaneously adapt to the interfacial bonding of the epoxy organic phase and the UHPC inorganic phase, resulting in insufficient long-term bond stability.

[0003] Therefore, there is a need for a UHPC-specific epoxy interface adhesive with wide temperature range curing, high wettability, high interfacial chemical bonding, high toughness, low shrinkage, and aging resistance to solve the problems existing in the application of interface adhesives to UHPC interfaces. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a high-bonding-toughness two-component epoxy interface adhesive for ultra-high performance concrete and its preparation method. Through customized component compounding and the synergistic effect of additives, the epoxy interface adhesive has the characteristics of wide temperature range curing, high wettability, high interfacial chemical bonding, high toughness, low shrinkage and aging resistance. It is suitable for splicing precast UHPC components, strengthening new and old UHPC structures, and bonding of UHPC and ordinary concrete composite interfaces.

[0005] This invention discloses a high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete, comprising component A and component B. Component A comprises, by weight, the following components: 80-120 parts bisphenol A type epoxy resin E-51, 10-20 parts reactive diluent, 5-15 parts telechelic reactive liquid rubber, 18-28 parts fumed silica, 0.5-3 parts wetting and dispersing agent, and 0.5-3 parts coupling agent. Component B comprises, by weight, the following components: 20-40 parts modified phenolic amine, 5-15 parts polyamide, and 0.5-3 parts accelerator.

[0006] Furthermore, the raw material of component A comprises the following components by weight: 100 parts of bisphenol A type epoxy resin E-51, 14 parts of reactive diluent, 10 parts of telechelic reactive liquid rubber, 22 parts of fumed silica, 1.5 parts of wetting and dispersing agent, and 1.5 parts of coupling agent; the raw material of component B comprises the following components by weight: 30 parts of modified phenolic amine, 10 parts of polyamide, and 1.5 parts of accelerator;

[0007] Furthermore, the reactive diluent is propylene oxide butyl ether; the telechelic reactive liquid rubber is carboxyl-terminated butadiene-acrylonitrile liquid rubber;

[0008] Furthermore, the wetting and dispersing agent is tetramethyldecynyl diol; the coupling agent is a silane coupling agent;

[0009] Furthermore, the accelerator is epoxy resin curing accelerator DMP-30, and the fumed silica is micron-sized fumed silica.

[0010] This invention also discloses a method for preparing a high-bond-toughness two-component epoxy interface adhesive for ultra-high performance concrete, characterized by comprising the following steps:

[0011] S1, Pre-reaction toughening modification: Bisphenol A type epoxy resin E-51 is grafted with remote claw type reactive liquid rubber to obtain modified epoxy matrix.

[0012] S2, add reactive diluent and fumed silica to the modified epoxy matrix and mix evenly, then add wetting and dispersing agent and coupling agent and mix evenly to obtain component A;

[0013] S3, component B is prepared by uniformly mixing modified phenolic amine, polyamide and accelerator.

[0014] Further, in step S1, the bisphenol A type epoxy resin E-51 is heated to 80-90°C, and then a remote claw type reactive liquid rubber is added and stirred. After the partial grafting reaction is completed, the temperature is lowered to below 40°C to obtain the modified epoxy matrix.

[0015] The beneficial effects of this invention are as follows: The high-adhesion toughness two-component epoxy interface adhesive for ultra-high performance concrete and its preparation method enhance the interfacial adhesion performance of UHPC from three aspects: impregnation, chemical bonding, and stress relief. This two-component epoxy interface adhesive can be cured normally at low temperature (0°C) and humid UHPC interfaces, achieving curing within a wide temperature range of 0~35°C. The adhesive can fully impregnate the dense microporous interface of UHPC, resulting in high toughness and a modulus that matches the UHPC matrix, forming a good match with the high modulus characteristics of UHPC. Under load, it can effectively disperse interfacial stress, avoiding brittle cracking of the adhesive layer. It has low curing shrinkage and a high retention rate of adhesion performance after freeze-thaw aging, with a bond strength retention rate still higher than 90% after 50 freeze-thaw cycles. Detailed Implementation

[0016] To better understand the present invention, the following embodiments are further illustrations of the present invention, but the content of the present invention is not limited to the following embodiments.

[0017] Unless otherwise specified, the experimental methods used in the embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.

[0018] This embodiment discloses a high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete, comprising component A and component B. Component A, by weight, comprises the following components: 80-120 parts of bisphenol A type epoxy resin E-51, 10-20 parts of reactive diluent, 5-15 parts of telechelic reactive liquid rubber, 18-28 parts of fumed silica, 0.5-3 parts of wetting and dispersing agent, and 0.5-3 parts of coupling agent. Component B, by weight, comprises the following components: 20-40 parts of modified phenolic amine, 5-15 parts of polyamide, and 0.5-3 parts of accelerator. By grafting bisphenol A type epoxy resin E-51 with telechelic reactive liquid rubber, compatibility is significantly improved, preventing macroscopic agglomeration of the rubber phase during subsequent overall curing. After curing, a uniformly distributed nanoscale island-shaped toughening structure is generated within the epoxy matrix. Under external forces, the rubber phase can induce crazes and shear bands, dissipating interfacial stress and significantly improving the elongation at break of the adhesive layer. The wetting and dispersing agent rapidly reduces the surface tension of the adhesive, allowing it to penetrate the nanoscale microporous structure of the UHPC surface, enhancing physical wetting and mechanical interlocking effects. Simultaneously, it eliminates micro-air bubbles trapped during mixing, preventing the formation of air bubble pores at the adhesive-concrete interface and eliminating weak points at the interface. The wetting and dispersing agent and coupling agent form an organic-inorganic chemical bond transition bridging layer; their synergy results in significantly higher interfacial bond strength than ordinary epoxy adhesives, fundamentally preventing the bonding interface from becoming a structurally weak area. Fumed silica, as a filler, can effectively reduce the volume shrinkage of the epoxy system during curing. In component B, modified phenolic amine and polyamide are combined as a curing system, retaining the advantages of modified phenolic amine in low-temperature curing and resistance to moisture-laden substrates, while leveraging the high toughness and high adhesion of the polyamide curing product. This interface adhesive can cure normally at 0℃ in humid UHPC interfaces, combining the characteristics of low-temperature rapid curing with the high toughness of the adhesive layer, overcoming the temperature limitations of ordinary epoxy adhesives for outdoor construction in winter. The modified phenolic amine used is T-31, which belongs to the modified phenolic amine (phenolic amine PAA) synthesized by the Mannich reaction; phenol, formaldehyde, and aliphatic amine (ethylenediamine) are condensed to obtain a low-molecular-weight amine curing agent.

[0019] In a preferred embodiment, the raw material of component A comprises the following components by weight: 100 parts of bisphenol A type epoxy resin E-51, 14 parts of reactive diluent, 10 parts of telechelic reactive liquid rubber, 22 parts of fumed silica, 1.5 parts of wetting and dispersing agent, and 1.5 parts of coupling agent; the raw material of component B comprises the following components by weight: 30 parts of modified phenolic amine, 10 parts of polyamide, and 1.5 parts of accelerator.

[0020] In this embodiment, the reactive diluent is propylene oxide butyl ether; the telechelic reactive liquid rubber is carboxyl-terminated butadiene-acrylonitrile liquid rubber CTBN; the wetting and dispersing agent is tetramethyldecynyl glycol; the coupling agent is silane coupling agent KH-560; the accelerator is epoxy resin curing accelerator DMP-30; and the fumed silica is micron-sized fumed silica N2O. The carboxyl-terminated liquid nitrile rubber CTBN is pre-reacted with E-51 epoxy resin, and the carboxyl and epoxy groups are partially ring-opened and grafted to avoid macroscopic agglomeration of the rubber phase during subsequent curing, forming a uniform nanoscale island toughening structure. The CTBN, after pre-grafting reaction, generates a uniform nanoscale island toughening phase with an elongation at break ≥8%. The high-toughness adhesive layer matches the modulus of the high-modulus UHPC matrix, effectively dispersing interfacial stress under external loads and alternating temperature loads, inhibiting brittle cracking of the adhesive layer, and significantly reducing the risk of interfacial debonding. The KH-560 molecule has an epoxy group at one end, which can covalently bond with the epoxy matrix; the alkoxy group at the other end, after hydrolysis, can dehydrate and condense with the silanol groups (-Si-OH) on the UHPC matrix surface to form siloxane bonds. This creates a molecular-level chemical bond transition layer between the organic epoxy layer and the inorganic UHPC substrate, meaning the organic-inorganic two phases no longer rely solely on physical adhesion; the chemical bonding significantly enhances the interfacial bonding strength.

[0021] This invention reconstitutes the curing system of component B by combining modified phenolic amine T31 with polyamide 650 and DMP-30 accelerators. This balances the relationship between curing speed, low-temperature activity, and adhesive toughness, making it suitable for outdoor application. Conventional techniques in the field involve using T31 alone (low-temperature curing, high brittleness) or polyamide 650 alone (high toughness, poor low-temperature curing); simple reconstitution of these two cannot achieve the synergistic effect of 0°C curability and high toughness.

[0022] This embodiment also discloses a method for preparing a high-bond-toughness two-component epoxy interface adhesive for ultra-high performance concrete, characterized by the following steps:

[0023] S1, Pre-reaction toughening modification: Bisphenol A type epoxy resin E-51 is grafted with remote claw type reactive liquid rubber to obtain modified epoxy matrix.

[0024] S2, add reactive diluent and fumed silica to the modified epoxy matrix and mix evenly, then add wetting and dispersing agent and coupling agent and mix evenly to obtain component A;

[0025] S3, component B is prepared by uniformly mixing modified phenolic amine, polyamide, and accelerator. The process is simple and controllable, and can achieve uniform nano-dispersion of the CTBN rubber phase, avoiding agglomeration defects.

[0026] In this embodiment, in step S1, bisphenol A type epoxy resin E-51 is heated to 80-90°C, then a remote claw type reactive liquid rubber is added and stirred. After partial grafting reaction, the temperature is lowered to below 40°C to obtain a modified epoxy body. The carboxyl-terminated liquid nitrile rubber (CTBN) belongs to the rubber phase. Without pre-reaction, nitrile rubber has poor thermodynamic compatibility with pure epoxy resin. If only simple physical blending at room temperature is performed, during epoxy curing and cross-linking, rubber segments will continuously migrate and aggregate, eventually forming millimeter-sized rubber agglomerates, resulting in surface spots and phase separation defects. After heating and pre-reaction, the -COOH groups on the CTBN molecular chain undergo partial grafting reactions with the epoxy groups of E-51, attaching a small amount of epoxy segments to a single rubber chain; thus generating an epoxy-CTBN graft copolymer. This graft copolymer acts as a "compatibility agent," inhibiting the mutual fusion and growth of rubber particles during subsequent overall curing, preventing macroscopic agglomeration of the rubber phase. Furthermore, the epoxy resin serves as the continuous phase (sea), while CTBN rubber particles act as the dispersed phase (islands). The pre-reaction process allows for precise control of the rubber phase particle size, maintaining the dispersed phase size within tens to two hundred nanometers, with particles uniformly distributed within the epoxy matrix. Without pre-reaction, the rubber island particles are coarse and uneven in size, with localized rubber enrichment and localized rubber deficiency, resulting in highly unstable toughening effects. After the reaction, the CTBN rubber particle surface is not simply physically embedded within the epoxy matrix; the surface of the rubber particles contains grafted epoxy segments, and chemical bonds exist between the rubber phase and the epoxy matrix. Under external force, the rubber particles are less prone to detachment and pull-out from the matrix, efficiently inducing crazes and shear yielding, dissipating fracture energy.

[0027] Example 1

[0028] The high-adhesion toughness two-component epoxy interface adhesive for ultra-high performance concrete in this embodiment comprises the following components by weight: 100 parts of bisphenol A type epoxy resin E-51, 30 parts of modified phenolic amine T31, 10 parts of polyamide 650, 1.5 parts of accelerator DMP-30, 14 parts of reactive diluent propylene oxide butyl ether, 10 parts of carboxyl-terminated liquid nitrile rubber CTBN, 22 parts of micron-sized fumed silica N20, 0.5 parts of wetting and dispersing agent tetramethyldecynyl diol, and 0.5 parts of silane coupling agent KH-560.

[0029] The preparation method includes the following steps:

[0030] S1. Pre-reaction toughening modification: Bisphenol A type epoxy resin E-51 was put into a reaction vessel with heating and stirring functions, heated to 85°C, and carboxyl-terminated liquid nitrile rubber CTBN was added. The mixture was stirred at 120 r / min for 2.5 hours. After the partial grafting reaction was completed, the mixture was naturally cooled to below 40°C to obtain the modified epoxy matrix.

[0031] S2. Base material dispersion and mixing: Add propylene oxide butyl ether to the above modified epoxy matrix, stir for 10 minutes to mix evenly, then add micron-sized fumed silica N20 in 3 batches, disperse at high speed at 800 r / min for 30 minutes to ensure that the filler is completely free of agglomeration; add tetramethyldecynyl glycol and KH-560 silane coupling agent in a set proportion to the dispersed base material, continue stirring for 15 minutes, filter and dispense to obtain component A;

[0032] S3. Preparation of curing agent components: Modified phenolic amine T31, polyamide 650 and DMP-30 are mixed evenly and stirred for 20 minutes before being dispensed to obtain component B;

[0033] S4. Finished Product Packaging: Seal and package components A and B separately according to the specified ratio to obtain the UHPC-specific epoxy interface adhesive finished product.

[0034] The specific application conditions for the above-mentioned UHPC-specific epoxy interface adhesive are as follows:

[0035] 1. Interface pretreatment: Grind the UHPC surface to be bonded to remove laitance, and blow away surface dust with high-pressure air to ensure that the interface is free of oil and loose particles;

[0036] 2. Adhesive preparation: Mix components A and B in a weight ratio of 147.5:41.5 and stir with an electric mixer for 3 to 5 minutes until the color is completely uniform. The amount of adhesive prepared should be used up within 30 minutes according to the construction speed.

[0037] 3. Application: Use a roller or scraper to evenly apply the mixed interface adhesive to the UHPC interface, controlling the adhesive layer thickness within the range of 0.3 to 0.8 mm to ensure that the adhesive fully penetrates into the micropores of the UHPC surface.

[0038] 4. Curing and hardening: When the ambient temperature is above 5℃, the initial bonding strength can be achieved in 24 hours and it will be fully cured in 7 days. In low temperature environments, the curing time can be extended appropriately. During the curing period, avoid stress on the interface and water immersion.

[0039] The performance of the high-adhesion-toughness two-component epoxy interface adhesive of this embodiment was tested, and the test results are as follows:

[0040] The adhesive has a contact angle of 32°, a 7-day interfacial splitting tensile strength of 4.2 MPa, and a 7-day shear strength of 7.8 MPa.

[0041] The amount of additives added in this embodiment is relatively low, and the effect of adhesive impregnation modification and chemical bonding improvement is limited. However, the bonding performance can meet the requirements of low-load bonding scenarios such as splicing and repair of UHPC components in a conventional indoor dry environment.

[0042] Example 2

[0043] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete uses 1 part tetramethyldecynylene glycol and 1 part KH-560, with the remaining components remaining unchanged. The preparation method is the same as in Example 1. Tests were conducted using the method described in Example 1, and the results are as follows:

[0044] The adhesive has a contact angle of 24°, a 7-day interfacial splitting tensile strength of 5.6 MPa, and a 7-day shear strength of 9.2 MPa.

[0045] This embodiment uses a medium-low additive ratio, and the wettability and coupling effects are initially demonstrated. The overall performance is balanced and it is suitable for most common UHPC reinforcement scenarios.

[0046] Example 3

[0047] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete contains 2 parts tetramethyldecynyl diol and 2 parts KH-560 in its formulation, with the remaining components remaining unchanged. The preparation method is the same as in Example 1. Tests were conducted using the same method as in Example 1, and the results are as follows:

[0048] The adhesive has a contact angle of 17°, a 7-day interfacial splitting tensile strength of 6.8 MPa, and a 7-day shear strength of 11.5 MPa.

[0049] This embodiment is the optimal embodiment of the additive. The adhesive can completely penetrate into the micropores of the UHPC surface, forming a complete chemical bond transition layer at the interface. The bonding strength exceeds the tensile strength of the UHPC body, achieving equal-strength bonding at the interface.

[0050] Example 4

[0051] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete contains 2.5 parts tetramethyldecynyl diol and 2.5 parts KH-560 in its formulation, with the remaining components remaining unchanged. The preparation method is the same as in Example 1. Tests were conducted using the method described in Example 1, and the results are as follows:

[0052] The adhesive has a contact angle of 15°, a 7-day interfacial splitting tensile strength of 6.3 MPa, and a 7-day shear strength of 10.7 MPa.

[0053] In this embodiment, a relatively high ratio of additives was used. Excessive wetting and dispersing agents caused slight oil separation on the surface of the adhesive layer, and the coupling agent self-polymerized to form a small amount of weak interface layer, resulting in a slight decrease in performance.

[0054] Example 5

[0055] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete contains 3 parts tetramethyldecynyl diol and 3 parts KH-560 in its formulation, with the remaining components remaining unchanged. The preparation method is the same as in Example 1. Tests were conducted using the same method as in Example 1, and the results are as follows:

[0056] The adhesive contact angle is 14°, the 7-day interfacial splitting tensile strength is 5.1 MPa, and the 7-day shear strength is 8.9 MPa.

[0057] This embodiment uses a high additive ratio. Excessive addition of additives leads to a decrease in the crosslinking density of the adhesive layer, resulting in a significant plasticizing effect and a slight decrease in mechanical properties.

[0058] Comparative Example

[0059] In this formulation, tetramethyldecynyl diol and KH-560 are not added; the remaining components are the same as in Example 1, and the preparation method is the same as in Example 1. Tests were conducted using the method described in Example 1, and the results are as follows:

[0060] The adhesive has a contact angle of 58°, a 7-day interfacial splitting tensile strength of 3.1 MPa, and a 7-day shear strength of 6.2 MPa. The adhesive is difficult to wet the dense surface of UHPC, and the interface relies solely on physical adsorption for bonding, which easily leads to interfacial delamination and debonding.

[0061] As can be seen from the results of the above embodiments, when the addition amounts of tetramethyldecynediol and KH-560 are both controlled at around 2 parts, the synergistic effect of the two reaches the optimal state, the overall bonding performance of the interface adhesive is the best, and it fully meets the high-strength bonding requirements of the UHPC structure.

[0062] Example 6

[0063] The high-adhesion toughness two-component epoxy interface adhesive for ultra-high performance concrete in this embodiment comprises the following components by weight: 80 parts of bisphenol A type epoxy resin E-51, 20 parts of modified phenolic amine T31, 5 parts of polyamide 650, 0.5 parts of accelerator DMP-30, 10 parts of reactive diluent propylene oxide butyl ether, 5 parts of carboxyl-terminated liquid nitrile rubber CTBN, 18 parts of micron-sized fumed silica N20, 2 parts of wetting and dispersing agent tetramethyldecynyl diol, and 2 parts of silane coupling agent KH-560.

[0064] The preparation method is the same as in Example 1, and the test was performed using the same method as in Example 1. The test results are as follows:

[0065] Test results: The adhesive contact angle was 18°, the 7-day interfacial splitting tensile strength was 5.2 MPa, and the 7-day interfacial shear strength was 9.0 MPa. The adhesive exhibited excellent wettability and interfacial chemical bonding, with the contact angle being essentially the same as that of the optimal example 3. However, the overall resin, toughening agent, curing agent, and filler dosages were reduced, resulting in a decrease in the system's crosslinking density and the number of island-type toughening structures. Consequently, the adhesive layer toughness and overall mechanical load-bearing capacity decreased slightly. This result still meets the requirements for conventional ordinary concrete and UHPC composite repair and low-load static bonding scenarios.

[0066] Example 7

[0067] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete comprises the following components by weight: 120 parts bisphenol A type epoxy resin E-51, 40 parts modified phenolic amine T31, 15 parts polyamide 650, 3 parts accelerator DMP-30, 20 parts reactive diluent propylene oxide butyl ether, 15 parts carboxyl-terminated liquid nitrile rubber CTBN, 28 parts micron-sized fumed silica N20, 2 parts wetting and dispersing agent tetramethyldecynyl glycol, and 2 parts silane coupling agent KH-560. The preparation method is the same as in Example 1. Testing was conducted using the method described in Example 1, and the results are as follows:

[0068] Test results: The adhesive contact angle was 16.5°, the 7-day interfacial splitting tensile strength was 6.5 MPa, and the 7-day interfacial shear strength was 10.9 MPa. Excellent wetting and coupling bonding effects were observed. The overall solid content of the system was increased, with simultaneous increases in the dosage of epoxy resin, toughening agent, curing agent, and filler. The density of the adhesive layer and the base strength were further improved. However, the excessive curing agent and toughening components slightly disrupted the crosslinking balance. Compared to the optimal formulation in Example 3, the mechanical properties decreased slightly, the adhesive viscosity was higher, and the construction wetting efficiency was slightly reduced. Overall, it still possesses excellent high-strength bonding performance, making it suitable for heavy-duty UHPC structure bonding scenarios.

[0069] Example 8

[0070] This embodiment of the high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete comprises the following components by weight: 90 parts bisphenol A type epoxy resin E-51, 40 parts modified phenolic amine T31, 8 parts polyamide 650, 1 part accelerator DMP-30, 20 parts reactive diluent propylene oxide butyl ether, 12 parts carboxyl-terminated liquid nitrile rubber CTBN, 20 parts micron-sized fumed silica N20, 2 parts wetting and dispersing agent tetramethyldecynyl glycol, and 2 parts silane coupling agent KH-560. The preparation method is the same as in Example 1. Testing was conducted using the method described in Example 1, and the results are as follows:

[0071] Test results: adhesive contact angle 17.2°, 7d interfacial splitting tensile strength 6.2MPa, 7d interfacial shear strength 10.5MPa.

[0072] The formulation of this embodiment has a balanced overall composition ratio, with a moderate increase in the amount of diluent and CTBN toughening agent, giving the adhesive layer good deformation adaptability and crack resistance. The high total amount of curing agent accelerates the crosslinking rate of the system, slightly offsetting some of the toughening effect. Compared with the optimal embodiment 3, the mechanical properties are slightly reduced, but the adhesive layer has excellent balance in toughness, construction fluidity, and interfacial bonding stability. It takes into account both low-temperature curing performance and fatigue durability, making it suitable for UHPC bridge reinforcement and splicing projects of new and old UHPC under outdoor temperature difference and frequent load.

[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A high-bond-toughness two-component epoxy interface adhesive for ultra-high performance concrete, characterized in that: The product comprises component A and component B. Component A, by weight, includes the following components: 80-120 parts of bisphenol A type epoxy resin E-51, 10-20 parts of reactive diluent, 5-15 parts of telechelic reactive liquid rubber, 18-28 parts of fumed silica, 0.5-3 parts of wetting and dispersing agent, and 0.5-3 parts of coupling agent. Component B, by weight, includes the following components: 20-40 parts of modified phenolic amine, 5-15 parts of polyamide, and 0.5-3 parts of accelerator.

2. The high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 1, characterized in that: The raw material of component A includes the following components by weight: 100 parts of bisphenol A type epoxy resin E-51, 14 parts of reactive diluent, 10 parts of telechelic reactive liquid rubber, 22 parts of fumed silica, 1.5 parts of wetting and dispersing agent, and 1.5 parts of coupling agent; the raw material of component B includes the following components by weight: 30 parts of modified phenolic amine, 10 parts of polyamide, and 1.5 parts of accelerator.

3. The high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 1, characterized in that: The reactive diluent is propylene oxide butyl ether; the telechelic reactive liquid rubber is carboxyl-terminated butadiene-acrylonitrile liquid rubber.

4. The high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 1, characterized in that: The wetting and dispersing agent is tetramethyldecynyl diol; the coupling agent is a silane coupling agent.

5. The high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 1, characterized in that: The accelerator is epoxy resin curing accelerator DMP-30, and the fumed silica is micron-sized fumed silica.

6. The method for preparing a high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 1, characterized in that: Includes the following steps: S1, Pre-reaction toughening modification: Bisphenol A type epoxy resin E-51 is grafted with remote claw type reactive liquid rubber to obtain modified epoxy matrix. S2, add reactive diluent and fumed silica to the modified epoxy matrix and mix evenly, then add wetting and dispersing agent and coupling agent and mix evenly to obtain component A; S3, component B is prepared by uniformly mixing modified phenolic amine, polyamide and accelerator.

7. The method for preparing a high-adhesion, high-toughness two-component epoxy interface adhesive for ultra-high performance concrete according to claim 6, characterized in that: In step S1, bisphenol A type epoxy resin E-51 is heated to 80-90°C, then a remote claw type reactive liquid rubber is added and stirred. After the partial grafting reaction is completed, the temperature is lowered to below 40°C to obtain the modified epoxy matrix.